Technique for suppression of background cascades produced by atmospheric muon bundles in the Baikal-GVD. (1st February 2022) - Allakhverdyan, V.A.; Avrorin, A.D.; Avrorin, A.V.; Aynutdinov, V.M.; Bannasch, R.; Bardačová, Z.; Belolaptikov, I.A.; Borina, I.V.; Brudanin, V.B.; Budnev, N.M.; Dik, V.Y.; Domogatsky, G.V.; et al.
Abstract: Baikal-GVD (Gigaton Volume Detector) is a neutrino telescope located in pure water of Lake Baikal. At the current stage (season 2021), detector is composed of 2304 optical modules arranged in 8 clusters. In searching for neutrino cascade events, light patterns produced via discrete stochastic energy losses along muon tracks create the most abundant background. Methods to separate cascade-like events from tracks and neutrino cascades in a single cluster have been developed and optimized. One of the method tries to find the maximum number of track hits amongst cascade hits, which are present in the muon bundle event. Other ones rely on the distributions of charges and positions of hits on optical modules associated with cascade events. All suppression methods were optimized by the Monte Carlo simulation datasets.